Capacity enhancement of virtual-mirror-based multiwavelength Brillouin-Erbium fiber laser. - Hitam, Salasiah; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir; Abd Rahman, Zubaidah; Al-Mansoori, Mohammed Hayder; Mahamd Adikan, Faisal Rafiq (2013)
An enhanced multiwavelength Brillouin-erbium fiber laser with virtual mirror concept is demonstrated. The performance of three linear amplifier schemes is investigated and optimized. Wide tuning range of 39 nm and maximum of nine laser lines are achieved utilizing a 915 nm pump laser at 616 mW pump power.